FUNCTION OF INTERCEPTION, EVAPOTRANSPIRATION AND ROOT REINFORCEMENT OF PLANT ON SLOPE STABILIZATION - Euthalia Hanggari Sittadewi (Jurnal Sains dan Teknologi Mitigasi Bencana, 2020)
The ability of plants to carry out the functions of interception, evapotranspiration and root reinforcement provides an effective and contributes to an increase in slope stability. Canopy has a role in the process of interception related to the reduction of amount the infiltrated water and the rapid fulfilment of soil moisture. Through the evapotranspiration mechanism, plants can reduce pore water pressure in the soil so that the trigger force for landslides can be reduced and the soil will be more stable. The roots mechanically strengthen the soil, through the transfer of shear stresses in the soil into tensile resistance in the roots. Roots also bind soil particles and increase surface roughness, thereby reducing the process of soil displacement or erosion. There is a positive relationship between the density of the tree canopy with the value of rainfall interception, evapotranspiration with a decrease in pore water pressure in the soil and the ability of root anchoring and binding with an increase in soil shear strength, indicating that the function of interception, evapotranspiration and strengthening of plant roots have a positive effect on increasing slope stability. Plants selection that considers the level of interception, the rate of evapotranspiration and root reinforcement by adjusting environmental and slopes conditions will determine the success of slope stabilization efforts by vegetative methods.Keywords : interception, evapotranspiration, root reinforcement, slope stabilization.